2022
DOI: 10.1002/cnr2.1722
|View full text |Cite
|
Sign up to set email alerts
|

Circulating LncRNAs landscape as potential biomarkers in breast cancer

Abstract: The delay in diagnosis and treatment of breast cancer results in low survival rates and high mortality. Thus, it is essential to characterize new therapeutic targets and prognostic breast cancer biomarkers. The rising evidence suggested that long non-coding RNAs (lncRNAs) expression levels are deregulated in human cancers and can use as biomarkers for the rapid diagnosis of breast cancer. In the present study, a Quantitative Real-time polymerase chain reaction (qRT-PCR) technique was used to measure twenty onc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Furthermore, UCA1 concentrations were measured to be even more elevated in the blood samples of patients in advanced stages, and women with lymph node and distant organ metastatic disease [ 4 , 5 ]. Nonetheless, one study found that UCA1 levels were not significantly correlated with clinicopathological characteristics, whereas another study proposed that UCA1 expression was reduced in left-sided MBC tumors, suggesting a potential correlation between UCA1 levels and laterality in MBC patients [ 2 , 30 ]. Almost all studies identified overexpressed UCA1 levels in BC tissues compared to the healthy ones, while additionally revealing the remarkable association of high UCA1 levels with short overall survival and advanced clinical stage disease [ 31 , 32 , 34 , 35 , 37 , 38 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, UCA1 concentrations were measured to be even more elevated in the blood samples of patients in advanced stages, and women with lymph node and distant organ metastatic disease [ 4 , 5 ]. Nonetheless, one study found that UCA1 levels were not significantly correlated with clinicopathological characteristics, whereas another study proposed that UCA1 expression was reduced in left-sided MBC tumors, suggesting a potential correlation between UCA1 levels and laterality in MBC patients [ 2 , 30 ]. Almost all studies identified overexpressed UCA1 levels in BC tissues compared to the healthy ones, while additionally revealing the remarkable association of high UCA1 levels with short overall survival and advanced clinical stage disease [ 31 , 32 , 34 , 35 , 37 , 38 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…After evaluating the expression of multiple lncRNAs in blood samples of untreated BC patients, Pourramezan et al identified that UCA1 was significantly upregulated in BC patients compared to healthy women; however, the correlation between UCA1 levels and clinicopathological characteristics, such as race, histological grade, tumor size, TNM staging, and molecular subtypes, was not statistically significant [ 30 ].…”
Section: The Role Of Uca1 In Bc Oncogenesis Proliferation and Invasionmentioning
confidence: 99%
“…Meanwhile, ROC curve reflected the possible diagnostic significance of MIR497HG. Through literature review, lncRNA BC040587 was verified to be low expressed in breast cancer, and related to some clinical indicators of patients (age, grade, metastasis), with the potential of diagnostic and prognostic indicators of breast cancer [ 21 ]. LncRNA NEAT1 levels decreased, and the ability of NEAT1 to differentiate breast cancer patients was confirmed by multivariate analysis and ROC method [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA H19 is also at the stage of clinical trials for glioblastoma, ovarian, bladder, and pancreatic cancer [267]. For breast cancer, a recent work of Pourramezan et al [268] established a list of fifteen circulating lncRNAs that are differentially expressed in BC patients compared to healthy women. They evidenced that the downregulation of the lncRNA NKILA and NBAT1 are linked to tumor size, whereas the blood concentration of H19 and SPRY4-IT1 is a good parameter to discriminate between BC patients and controls.…”
Section: Discussionmentioning
confidence: 99%